Adoption and Impact of SWAYAM Courses Among NCR College Students: Adopsi dan Dampak Kursus SWAYAM di Kalangan Mahasiswa Perguruan Tinggi NCR - Rajni Bala (Yayasan Nurul Musthafa, 2026)
This study focus to analyze the extent and patterns of SWAYAM (Study Webs of Active-learning for Young Aspiring Minds) courses among college students in the National Capital Region (NCR). A purposive sampling technique was used to collect data through a questionnaire circulated as a Google form. A total of 112 college students constituted sample for study. The findings suggest that the majority of students (83.93%) showed interest in SWAYAM courses, while 16.07% expressed no interest. Additionally, 80.36% were willing to register in SWAYAM courses. However, only 22.32% of respondents had literally registered, with 77.68% yet to participate. Regarding familiarity, 61.60% of college students were aware of MOOCs, whereas 38.39% lacked awareness, indicating a significant knowledge gap. Opinions on the effectiveness of SWAYAM courses revealed that 41.07% perceived them as less effective than traditional learning methods, while 58.93% disagreed with this view. The main challenges reported were time management, with 64.28% reported it difficult to manage SWAYAM courses with their academic schedules. Also there is need of training as 63.39% felt challenged without prior training. [Studi ini berfokus untuk menganalisis sejauh mana pola penggunaan kursus SWAYAM (Study Webs of Active-learning for Young Aspiring Minds) di kalangan mahasiswa perguruan tinggi di National Capital Region (NCR). Teknik purposive sampling digunakan untuk mengumpulkan data melalui kuesioner yang disebarkan dalam bentuk Google Form. Sebanyak 112 mahasiswa perguruan tinggi menjadi sampel dalam studi ini. Temuan menunjukkan bahwa mayoritas mahasiswa (83,93%) menunjukkan minat pada kursus SWAYAM, sementara 16,07% menyatakan tidak berminat. Selain itu, 80,36% bersedia mendaftar di kursus SWAYAM. Namun, hanya 22,32% responden yang benar-benar telah mendaftar, sementara 77,68% sisanya belum berpartisipasi. Terkait keakraban dengan platform, 61,60% mahasiswa mengetahui tentang MOOCs (Massive Open Online Courses), sedangkan 38,39% kurang mengetahuinya, yang mengindikasikan adanya celah pengetahuan yang signifikan. Opini mengenai efektivitas kursus SWAYAM mengungkapkan bahwa 41,07% menganggap kursus tersebut kurang efektif dibandingkan metode pembelajaran tradisional, sementara 58,93% tidak setuju dengan pandangan tersebut. Tantangan utama yang dilaporkan adalah manajemen waktu, di mana 64,28% merasa sulit untuk mengatur waktu antara kursus SWAYAM dengan jadwal akademik mereka. Selain itu, terdapat kebutuhan akan pelatihan karena 63,39% merasa kesulitan tanpa adanya pelatihan terlebih dahulu.]